If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1.093x + 1) = 6 Reorder the terms: 5(1 + 1.093x) = 6 (1 * 5 + 1.093x * 5) = 6 (5 + 5.465x) = 6 Solving 5 + 5.465x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 5.465x = 6 + -5 Combine like terms: 5 + -5 = 0 0 + 5.465x = 6 + -5 5.465x = 6 + -5 Combine like terms: 6 + -5 = 1 5.465x = 1 Divide each side by '5.465'. x = 0.1829826167 Simplifying x = 0.1829826167
| h-h+3h+3h+4h-9=11 | | x^2/2+3x/2=4 | | 15y-6y-3y-5y+2y+1=19 | | 5a(16a^2+24a+9)= | | x^4+12x^3+36x^2=-5 | | 7(1.055x+1)=13 | | 4x-8y-9x+5y= | | 4p+2p-3p+3p=18 | | -11m+17m+14m+18=-2 | | x^4+12x^3+36x^2+5=0 | | 19g-7g-9g=12 | | 2y=-5x-13 | | 20c-17c-2c=9 | | 40/5+4*2-5 | | 9y^2-30y=-23 | | 10d-12d-10d+15d=-9 | | a-1/7=2/3 | | 9y^2-30y=0 | | 10x^2-4x=-21 | | 3(8+a)=12 | | 9t^2-12t=-4 | | 5(y+7)=7y+35 | | 7,700-201/2 | | 20g-2g-16g=20 | | 6r-3r-r+3r-2r=9 | | 3(x+1.42)=2x | | -15z-12z+10z-2z+9z=-14 | | x^2-4x=27 | | 5n+n-3n+4n=7 | | 10u+2u-4u=16 | | 12x^2-4x=11 | | 20n-19n=18 |